INCORPORATING NATIONAL CULTURE INTO VISUAL ARTS LESSONS TO FOSTER STUDENTS’ CREATIVITY - Nasulloyeva Sarvinoz Komiljon qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores methods for incorporating national culture into visual arts lessons to foster students’ creativity and aesthetic literacy. It emphasizes the role of traditional art forms in developing artistic skills, cultural awareness, and creative thinking. The study discusses practical, project-based, and interactive pedagogical strategies that allow students to apply national and traditional art elements in modern visual art projects, enhancing engagement and learning outcomes.